PENGGUNAAN MEDIA POP-UP BOOK PADA MATERI PEREDARAN DARAHKU SEHAT UNTUK MENINGKATKAN KOGNITIF SISWA KELAS V SD NEGERI DAMAI - Nasri Diana (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2023)
The aim of this research was to find out whether the use of pop-up book media could improved the learning outcomes of 5th grade students on the material my blood circulation is healthy. These research was classroom action research carried out in two cycles. Each cycle consists of four stages, which are planning, acting, observing and reflecting. The subjects of this research were 12 students consisting of 5 boys and 7 girls. Data collection methods were observation, test/evaluation and documentation. Student learning outcomes in cycle I obtained 58.33% of students who completed their studies with an average score of 70.83. And it increased in cycle II to 83.33% of students who completed their studies with an average score of 81.91. So it can be said that there is an increase in student learning outcomes in the material about my healthy blood circulation using pop-up book media in class V of SD Negeri Damai